Effect of tibial rotational alignment and posterior slope on joint biomechanics in posterior-stabilized total knee arthroplasty: a finite element study - Long Shao; Xiangdong Wu; Chaohua Fang; Hongli Zhu; Kun Tao; Shicheng Wang (European Journal of Medical Research)
Abstract Background This study aims to clarify the combined influence of the tibial rotational alignment and posterior slope on knee joint biomechanics after posterior-stabilized total knee arthroplasty using a computer simulation. Methods Computer tomographic and magnetic resonance imaging scan of a healthy volunteer were used to reconstruct a detailed 3D geometrical model. A virtual surgery was performed to generate a resection plane with different posterior slopes and rotational alignment on the proximal tibia. The internal, neutral and external rotation, combined with a posterior slope of 0, 3, 5, and 7 degrees were simulated for both standing and bending position. The differences in contact pressure, area and stress of polyethene liner and the tensile stress of the soft tissue were compared. Results The contact area on the polyethylene liner decreased with increasing posterior slope in a standing position while the opposite trend was found in a bending position. In a bending position, internal rotation of tibial component resulted in smaller contact areas than neutral or external rotation. A posterior slope of 0° combined with neutral rotation in a standing position showed the smallest pressure on the liner with biggest contact area. The distribution of von Mises stress was more uniform with 0° and 3° than 5° and 7° posterior tibial slope for both standing and bending position. The stress increased with increasing posterior slope in both standing and bending position, ranging from 8.77 MPa to 79.39 MPa. The ligament and muscle tensile stress increased with increasing posterior slope in both standing and bending position. In addition, the neutral rotation showed lower maximum stress compared with other rotational alignment in a standing position. Conclusions An increased posterior slope increases the contact pressure and stress of the polyethene liner and the ligament tensile stress. A neutral rotation combined with a posterior slope of less than 3° showed superior biomechanical results in posterior-stabilized TKA.